2014
DOI: 10.4314/star.v2i4.15
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Cow Urine against <i>Colletotrichum capsici</i> Isolated from Anthracnose of Chilli (<i>Capsicum annuum L.</i>)

Abstract: Article InformationCow urine has got several applications in agriculture. It is shown to possess inhibitory activity against many phytopathogenic fungi and bacteria. Among various diseases of Chilli, anthracnose is the most important disease which results in drastic reduction in yield. The present study was conducted with an aim to determine antifungal efficacy of cow urine against Colletotrichum capsici isolated from anthracnose of chilli (Capsicum annuum L.). Poisoned food technique was employed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Cow urine has immense applications in agriculture, for example antifungal and insecticidal, as revealed by several literatures [8,[20][21][22][23][24]. Formulations containing cow urine and plants have been shown to display mycelial growth inhibitory activity against a range of phytopathogenic fungi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cow urine has immense applications in agriculture, for example antifungal and insecticidal, as revealed by several literatures [8,[20][21][22][23][24]. Formulations containing cow urine and plants have been shown to display mycelial growth inhibitory activity against a range of phytopathogenic fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Natural products including cow urine and cow urine based formulations have been investigated for antifungal activity and the results appeared promising [1][2][3][4][5]. Cow urine is shown to exhibit potent inhibitory activity against a wide range of pathogenic microbes including phytopathogenic fungi [3,4,[6][7][8][9][10][11]. Similarly, formulations based on cow urine and plants have shown to possess inhibitory effect against various pathogenic microorganisms [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The anthracnose disease is caused by Colletotrichum species. Among various species implicated in causing anthracnose of chilli, C. capsici is the most important pathogen (Ushakiran et al, 2006;Anand et al, 2007;Ratanacherdchai et al, 2007;Than et al, 2008;Narasimhan and Shivakumar, 2012;Masoodi et al, 2013;Kambar et al, 2013). In the present study, we investigated antifungal effect of extracts of different parts of P. longifolia, G. glauca and A. lawii against C. capsici isolated from anthracnose of chilli by poisoned food technique.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated antifungal effect of extracts of different parts of P. longifolia, G. glauca and A. lawii against C. capsici isolated from anthracnose of chilli by poisoned food technique. This technique is widely used to evaluate antifungal activity of a variety of samples including plant extracts (Chutia et al, 2009;Farooq et al, 2010;Rakesh et al, 2013;Kambar et al, 2013). Extracts of P. longifolia exhibited higher inhibition of mycelial growth of C. capsici followed by A. lawii and G. glauca.…”
Section: Discussionmentioning
confidence: 99%
“…Rahman et al, (2005) also reported Garlic extracts to be the best for controlling pre-dominant fungi of chilli followed by Neem and Ginger. Kambar et al, (2013) reported the inhibitory effect of cow urine against C. capsici under the in vitro study. Ushakiran et al, (2006) also reported high inhibitory effect of the Garlic extract on the growth of the fungi causing fruit rot of chilli.…”
Section: Effect Of Plant Extracts On the Growth Of Ccapsici In Vitromentioning
confidence: 99%